Accurate light microscopic diagnosis of South‐East Asian ovalocytosis. (13th July 2018) - Nixon, Christian P.; Satyagraha, Ari W.; Baird, Grayson L.; Harahap, Alida R.; Panggalo, Lydia V.; Ekawati, Lenny L.; Sutanto, Inge; Syafruddin, Din; Kevin Baird, J.
Abstract: Introduction: South‐East Asian ovalocytosis (SAO) is a common inherited red blood cell polymorphism in South‐East Asian and Melanesian populations, coinciding with areas of malaria endemicity. Validation of light microscopy as a diagnostic alternative to molecular genotyping may allow for its cost‐effective use either prospectively or retrospectively by analysis of archived blood smears. Methods: We assessed light microscopic diagnosis of SAO compared to standard PCR genotyping. Three trained microscopists each assessed the same 971 Giemsa‐stained thin blood films for which SAO genotypic confirmation was available by PCR. Generalized mixed modeling was used to estimate the sensitivity, specificity, positive predictive value, and negative predictive value of light microscopy vs "gold standard" PCR. Results: Among red cell morphologic parameters evaluated, knizocytes, rather than ovalocytic morphology, proved the strongest predictor of SAO status (odds ratio [OR] = 19.2; 95% confidence interval [95% CI] = 14.6‐25.3; P ≤ 0.0001). The diagnostic performance of a knizocyte‐centric microscopic approach was microscopist dependent: two microscopists applied this approach with a sensitivity of 0.89 and a specificity of 0.93. Inter‐rater reliability among the microscopists (κ = 0.20) as well as between gold standard and microscopist (κ = 0.36) underperformed due to misclassification of stomatocytes as knizocytes by one microscopist, but improved substantially when excluding the error‐prone reader (κ = 0.65 and 0.74, respectively). Conclusion: Light microscopic diagnosis of SAO by knizocyte visual cue performed comparable to time‐consuming and costlier molecular methods, but requires specific training that includes successful differentiation of knizocytes from stomatocytes.